Detection of human papilloma virus by «Self sampling»: a new model of cervical cancer screening - O. O. Kovalyov; N. N. Voloshina; A. M. Riaboshapka; K. A. Kovalyov (Сучасні медичні технології)
The article presents the advantages of screening cervical cancer based on the detection of oncogenic strains of human papillomavirus compare to traditional cytological screening using the PAP test. Self sampling using Aprovix's Qvintip tool (Sweden) allows to increase the percentage of women participating in national population screening programs, which will lead to an improvement in the incidence and mortality rates of the female population from cervical cancer.